1998
DOI: 10.1677/joe.0.1580161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of ACTH in the regulation of adrenal responsiveness and the timing of parturition in the ovine fetus

Abstract: A dramatic late-gestation increase in fetal plasma cortisol concentrations is critical for the timing of parturition in the sheep. This increase appears to depend upon an intact hypothalamo-pituitary unit and is characterised by increasing responsiveness of the fetal adrenal gland to ACTH. ACTH has been postulated as the critical determinant of the late-gestation cortisol increase; however, recent evidence has suggested that other factors, including the ACTH precursor, pro-opiomelanocortin, may also be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
3
21
1
Order By: Relevance
“…The relatively constant concentrations of ACTH 1-39 during the infusion period are consistent with those previously reported during this window of gestation (21) and are also consistent with the concept that adrenocortical maturation in fetal sheep largely takes place in the presence of relatively steady basal levels of ACTH during late gestation (32). The lack of effect of the leptin antagonist on ACTH 1-39 , compared with the inhibitory actions of exogenous leptin previously noted in fetal sheep, may relate to the gestational age of the animals in the present study and the mode of administration (peripheral vs. central) of the leptin antagonist.…”
Section: Discussionsupporting
confidence: 90%
“…The relatively constant concentrations of ACTH 1-39 during the infusion period are consistent with those previously reported during this window of gestation (21) and are also consistent with the concept that adrenocortical maturation in fetal sheep largely takes place in the presence of relatively steady basal levels of ACTH during late gestation (32). The lack of effect of the leptin antagonist on ACTH 1-39 , compared with the inhibitory actions of exogenous leptin previously noted in fetal sheep, may relate to the gestational age of the animals in the present study and the mode of administration (peripheral vs. central) of the leptin antagonist.…”
Section: Discussionsupporting
confidence: 90%
“…LPS-induced tumor necrosis factor (TNF)-· and interleukin (IL)-1 can signal the central nervous system and stimulate corticotrophinreleasing hormone release into the hypophyseal portal veins that transport it to the anterior pituitary gland where it stimulates the release of adrenocorticotropic hormone from the corticotropes [1]. Adrenocorticotropic hormone circulates to the adrenal cortex and stimulates the release of glucocorticoids [9]. LPS also alters the secretion of other pituitary hormones, increasing prolactin (PRL) release and decreasing growth hormone and luteinizing hormone release [5].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of immunoreactive, ACTH-related peptides with corticotropic, unchanged or anticorticotropic biological activity has been demonstrated in plasma and pituitaries of intact fetuses [10, 23, 34, 35, 36, 37, 38, 39, 40, 41]and it has been speculated that this immunoreactivity may correspond to high molecular weight (MW) ACTH precursors [20, 38, 42, 43]. We have previously demonstrated that the HPD fetus has normal concentrations of both low and high MW ACTH-containing peptides by chromatography [13]and by two site immunoradiometric assays at days 130–140 GA [38, 44]and we now report an apparently identical biological scenario in intact fetuses using a radioimmunoassay that appears to preferentially bind low MW ACTH-immunoreactive species (our unpublished data based on assay of gel chromatography eluates from fetal plasma). The presence of immunoreactive, but not bioactive, ACTH in the intact fetal sheep circulation could explain the apparent lack of congruence of ir-ACTH and cortisol concentrations that has been reported in fetal sheep in this and many other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The secretory dynamics of ir-ACTH and cortisol were assessed by deconvolution analysis [27]at day 138 GA using samples drawn 5 min apart over 3 h [15]. At day 140 GA the adrenal response to a standard dose of ACTH 1–24 (2.5 µg/kg) was determined [13, 14]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation